금속기지 내열 경사기능 복합재료 개발에 관한 연구 - 김부안(Bu Ahn Kim); 남기우(Ki Woo Nam); 조문호(Mun Ho Cho) (Han-guk haeyang gonghak hoeji (Online), 1999)
67Ni-22Cr-10Al-1Y and $ZrO_2-8Y_2O_3$ were coated on the substrate surface of ST304 and Al2024 by the plasma spraying method. The adgesion of the films varies depending on the substrates and the laminating method. In the case of STS304, the cracks were observed at thermal shock temperature difference ${Delta}T$ of $900^{circ}C$ in the non functionally gradient material(NFGM) and at $1100^{circ}C$ in the functionally gradient material(FGM). The film adhesion of the FGM is better than that of the NFGM in ST304. The cumulative AE count of the FGM of STS304 increased continuously at the bending test. But the NFGM of STS304 showed discontinuity of the AE count. The total AE count for the FGM of STS304 decreased as the number of thermal shock increased, and this tendency was evident as the thermal shock temperature difference increased.